2007
DOI: 10.1007/s10338-007-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental researches on magneto-thermo-mechanical characterization of Terfenol-D

Abstract: The coupling effects of axial pre-stress, temperature and magnetic field on magnetostrictive strain and magnetization as well as Young's modulus of a Terfenol-D (Tb0.3Dy0.7Fe1.93) rod are tested to give a good understanding of magneto-thermal-mecha-nical characteristics of giant magnetostrictive materials. Results show that magneto-thermo-mechanical coupling of giant magnetostrictive materials is very strong; and the influences of pre-stress and temperature on magnetostrictive strain and Young's modulus vary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 9 publications
4
31
0
Order By: Relevance
“…It can seen from Fig. 1, the predictions of magnetostrictive strain curves under different compressive pre-stresses coincide well with Liang's experimental results 8 qualitatively and quantitatively not only in the region of low and moderate magnetic field but also in the region of high field. Meanwhile, it also can be found that magnetostrictive strain increases with increasing magnetic field under a given compressive pre-stress; the magnetostrictive strain decreases with the increase of compressive pre-stress in the region of low bias field; while a larger compressive pre-stress can achieve a greater magnetostrictive strain of Terfenol-D when the magnetic field is high enough to achieve saturation magnetization.…”
Section: Quantitative Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It can seen from Fig. 1, the predictions of magnetostrictive strain curves under different compressive pre-stresses coincide well with Liang's experimental results 8 qualitatively and quantitatively not only in the region of low and moderate magnetic field but also in the region of high field. Meanwhile, it also can be found that magnetostrictive strain increases with increasing magnetic field under a given compressive pre-stress; the magnetostrictive strain decreases with the increase of compressive pre-stress in the region of low bias field; while a larger compressive pre-stress can achieve a greater magnetostrictive strain of Terfenol-D when the magnetic field is high enough to achieve saturation magnetization.…”
Section: Quantitative Discussionsupporting
confidence: 75%
“…First, magnetostrictive strain curves measured by Liang et al 8 under different compressive pre-stresses are selected due to the completeness and clarity of the results. Since the concrete material parameters are not provided in the experiment of Liang et al, 8 the optimal parameters are selected as λ s = 1600ppm, µ 0 M s = 1.15T, χ m = 35, σ λ = 150MPa. At this basis, the comparison between the predicted magnetostrictive strain by this constitutive model and the experimental result is shown in Fig.…”
Section: Quantitative Discussionmentioning
confidence: 99%
“…Most of the time, the temperature is induced by chambers (5) or electrical heating (6) , which makes it necessary to develop new experimental apparatus to provide reliable and high magnetic, stress and temperature fields at the same time. The lack of systematical multi-field experimental results is also an obstacle to magneto-thermo-mechanical theoretical works (7) (8) .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] However, the nonlinear constitutive model of magnetostrictive phase is complex and not intuitive for building an equivalent circuit model, so it is replaced by the magnetostrictive constitutive model with variable coefficients in this paper. Without regard to the thermal expansion effect, the constitutive equations are expressed as:…”
Section: The Establishment Of Modelmentioning
confidence: 99%
“…Now, many researchers dedicate to improving the linearity of the CME effect. 19 However, the magnetization and magnetostriction of the ferromagnetic materials show the strong nonlinear thermo-magneto-mechanical coupling characteristic [20][21][22][23] under the influences of bias magnetic field, pre-stress and temperature, which lead to the CME effect and the electric field controlled magnetization effect possessing the strong nonlinear coupling effects essentially. Thus, to carry out a research about the nonlinear converse magnetoelectric coupling effect under the multi-physical field loadings is very urgent and necessary.…”
Section: Introductionmentioning
confidence: 99%